E-Module Research Trends in Learning Physics: Bibliometric Studies in 2017-2021 Range (Before and During the COVID-19 Pandemic) - Zainuddin Zainuddin; Surya Haryandi; Misbah Misbah; Winda Febriani; Siti Aisyah; Nida Supiati; Mohd Ali Ibrahim (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2022)
The COVID-19 pandemic that has hit the world for the past two years has created a new trend in the world of education, one of which is through the use of e-modules. The purpose of this research is to identify and describe trends in e-module research in physics learning. The method used in this research is through bibliometric studies. The research was conducted by searching online through the Scopus database in July 2022 with the keyword